Pendidikan Islam dan Bahasa Daerah: Penguatan Makna Kitab Nadhoman Tarbiyatus Sibyan dan Relevansinya di Era Kontemporer - Qomariyah, Nurul (Ngaji: Jurnal Pendidikan Islam, 2025)
The book Nadhoman Tarbiyatus Sibyan, which contains the basic teachings of the Islamic religion for children, has an important role in forming religious and moral foundations from an early age. This research uses a qualitative approach with content analysis methods to examine the translation of the book, as well as in-depth interviews with religious and language education experts. The research results show that the translation of the Book of Nadhoman Tarbiyatus Sibyan not only helps in understanding religious texts, but also strengthens the teaching of Arabic as a language of instruction for religious knowledge. This research found that an appropriate translation approach can increase students’ absorption and appreciation of religious material. Apart from that, in the context of the contemporary era which is filled with the challenges of modernization and globalization, the Book of Nadhoman Tarbiyatus Sibyan plays an important role in maintaining religious values ​​and cultural identity. The relevance of this book in the contemporary era lies in its ability to answer new challenges in religious education, such as the integration of technology in learning and increasing religious literacy among the younger generation.   Abstrak: Kitab Nadhoman Tarbiyatus Sibyan, yang berisi ajaran-ajaran dasar agama Islam untuk anak-anak, memiliki peran penting dalam membentuk fondasi keagamaan dan moral sejak dini. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi untuk mengkaji terjemahan kitab tersebut, serta wawancara mendalam dengan para ahli pendidikan agama dan bahasa. Hasil penelitian menunjukkan bahwa terjemahan Kitab Nadhoman Tarbiyatus Sibyan tidak hanya membantu dalam pemahaman teks-teks keagamaan, tetapi juga memperkuat pengajaran bahasa Arab sebagai bahasa pengantar ilmu agama. Penelitian ini menemukan bahwa pendekatan terjemahan yang tepat dapat meningkatkan daya serap dan apresiasi siswa terhadap materi keagamaan. Selain itu, dalam konteks era kontemporer yang dipenuhi dengan tantangan modernisasi dan globalisasi, Kitab Nadhoman Tarbiyatus Sibyan berperan penting dalam menjaga nilai-nilai keagamaan dan identitas budaya. Relevansi kitab ini di era kontemporer terletak pada kemampuannya untuk menjawab tantangan-tantangan baru dalam pendidikan agama, seperti integrasi teknologi dalam pembelajaran dan peningkatan literasi keagamaan di kalangan generasi muda. Kata kunci: Pendidikan Islam, Kitab Nadhoman Tarbiyatus Sibyan, relevansi pendidikan kontemporer